The Effect of Audio-Visual Education on Foot Care Knowledge in Preventing Diabetic Foot Ulcers among Patients with Diabetes Mellitus at Pekauman Primary Health Center, Banjarmasin - Hanafi, Muhammad Iqbal; Hadrianti, Dessy; Saherna, Jenny; Afriyanti, Uni (Fakultas Kedokteran, Universitas Papua, 2025)
Diabetes mellitus can lead to serious complications, including diabetic foot ulcers (DFUs), which carry a high risk of disability and amputation. This study aimed to analyze the effect of audio-visual education on foot care knowledge among patients with diabetes mellitus at the Pekauman Primary Health Center, Banjarmasin. This study employed a quasi-experimental one-group pretest–posttest design and involved 103 patients selected from a population of 215 patients (December 2024) using accidental sampling. Inclusion criteria comprised newly diagnosed or follow-up patients, individuals with compos mentis status, and adults. The research instrument was the Nottingham Assessment of Functional Footcare (NAFF) questionnaire consisting of 29 items, which was validated and found to be reliable. The intervention consisted of a ±10-minute animated video demonstrating six steps of diabetic foot care. Data were analyzed using the Wilcoxon signed-rank test to assess changes in knowledge levels. The results showed a significant improvement in knowledge (p < 0.001): prior to the intervention, 98.1% of respondents had “Poor” knowledge, whereas after the intervention, 99.0% demonstrated “Good” knowledge. Therefore, audio-visual education is effective in improving foot care knowledge and can be implemented as a primary health promotion strategy to prevent diabetic foot ulcers.